Relationship Of Knowledge And Attitude Of Pregnant Mothers With Pregnancy Examination (Anc K4) In Environment Iii Kelurahan Baru Ladang Bambu, Tuntunan District - Nurdiana Manurung; Arva Rochmawati (Institute of Computer Science (IOCS), 2020)
The coverage of K4 pregnant women's visits in Indonesia in 2013 was 86.52%, it means that the Strategic Plan target in 2013 was 93%. Antenatal care is care given to pregnant women from confirmation of conception to early delivery. This study aims to determine the relationship between knowledge and attitudes of pregnant women with antenatal care (ANC K4). The research method used iscross sectional, where the population is all pregnant women who perform antenatal care (ANC K4) in Environment III Kel. Baru Ladang Bambu Kec. Medan Tuntungan in 2020 a total of 61 respondents. The sample size is 30 respondents with purposive sampling technique. The results of the analysis showed that 5 respondents who had good knowledge and the majority of positive attitudes were in accordance with the standards in conducting pregnancy tests (ANC K4) 16.7%, 14 respondents who had sufficient knowledge and the majority of positive attitudes were in accordance with the standards in conducting pregnancy tests (ANC K4). 43.3%, and of the 11 respondents who had less knowledge and the majority of negative attitudes were not in accordance with the standards in carrying out pregnancy tests (ANC K4) 40%. The results of the Chi-square statistical test obtained p = 0, 000, which means that there is a relationship between knowledge and attitude with pregnancy examination (ANC K4). It is hoped that pregnant women will continue to carry out antenatal visits (ANC K4) during pregnancy.